Activin A is deeply involved in the progression of sarcopenia and leads to poor prognosis in lung cancer patients - Yo Kawaguchi; Yoko Kataoka; Keigo Okamoto; Makoto Yoden; Takuya Shiratori; Ryosuke Kaku; Keiko Ueda; Yasuhiko Ohshio; Tomoya Terashima; Jun Hanaoka (Scientific Reports)
Abstract Patients with lung cancer frequently develop sarcopenia, which severely affects quality of life. The underlying mechanisms of lung cancer sarcopenia need to be clarified because sarcopenia is strongly correlated with poor prognosis. Here, we focused on lung cancer-derived activin A, which catabolizes skeletal muscles, and aimed to clarify the mechanisms that lead to a poor prognosis. Immunohistochemistry of activin A in human resected lung cancer tissues has demonstrated that higher activin A expression leads to lower skeletal muscle mass and poor prognosis in patients with lung cancer. Transplantation of Lewis lung carcinoma (LLC) cells to mouse models induced the elevation of serum activin A level, resulting in skeletal muscle atrophy and reduced grip strength. We performed knock-down experiments of activin A in LLC cells. When mice were transplanted with activin A knock-down LLC cells, the serum activin A level decreased, and skeletal muscle volume and grip strength recovered. Furthermore, tumor growth was suppressed, and survival was prolonged in activin A knock-down LLC bearing mice. Mechanistically, activin A recruits macrophages into the tumor microenvironment to differentiate them into tumor-promoting macrophages. This study indicated that interfering with the effect of activin A can be a therapeutic target for sarcopenia and lung cancer progression.